PEMBERIAN EDUKASI GIZI DAN PSIKOLOGI PERKEMBANGAN ANAK KEPADA ORANGTUA SISWA DI SD INPRES OEPURA 3 KOTA KUPANG - Santa da Costa; Anita Sembiring; Jane Peni (Pergizi Pangan DPD NTT, 2023)
School-age children are children aged between 6-12 years. The 6-12 years period is a time when children experience rapid growth and development. Foods that contain nutritional elements are needed for the growth and development process of children. The 2018 Riskesdas results show that nutrition problems in school-age children need attention from all parties. In NTT, the prevalence of very short and short in children aged 5-12 years reached 41.1%, very thin and thin reached 18.5%, and fat and obese 6.1%. One of the efforts to improve the nutritional status of school children is to provide education to parents about balanced nutrition and child development psychology so that there is an increase in maternal knowledge and children's nutritional status. Baseline results at SD Impres Oepura 3 parents have never done nutritional status screening and education on balanced nutrition and psychology of school children's development. The purpose of this community service is to increase parents' knowledge about balanced nutrition and child development psychology and have a picture of the nutritional status of elementary school students. Activities were carried out at SD Inpres Oepura 3. Activities were carried out in the form of counseling using lecture methods and pocket book tools involving parents. Evaluation of activities is carried out in the form of pre-post tests. The results of education have increased parental knowledge by 81.5%.